Children’s Participation Rights in Practice: Exploring Circle Time as a Space for Participation in Preschool Classrooms - Karan, Şeyda; Erden, Feyza Tantekin (Routledge, 2026)
Children’s Participation Rights (CPR) are central to international policy debates on early childhood education. However, the practical enactment remains contested due to complex adult– child interactions across contexts. This context-sensitive investigation examines Turkish preschool classrooms. Using a multiple case study design, it explores verbal teacher–child interactions during 16 h of circle time observations with two teachers and 45 children (60–72 months). Framed within Lundy’s Participation Model, deductive reflexive thematic analysis highlights that structural arrangements of the classroom environment and procedural practices of teacher–child interactions simultaneously function to make circle time a potentially participatory space. The findings affirm that the activation of CPR in practice mostly depends on teachers’ dispositions, internal pedagogical practices, and the facilitation of an active listening environment. Children’s expressions were mostly limited to teacher sanctions, reducing chances to incorporate their views into decision-making. Findings also revealed that teachers’ recognition of their internal barriers is equally as decisive as external constraints in shaping CPR enactment. By outlining complexities of CPR in practice, this study advances understanding of the pedagogical insights for reconsidering everyday routines as sites of participation, improving educational quality. It also informs future research for genuinely participatory educational environments.
Keywords: Children’s Participation Rights; Circle Time; Preschool Classrooms; Teacher-Child İnteractions; Lundy’s Participation Model; Quality Education